Acurácia diagnóstica de definições de casos de periodontite severa - Brito, Liana Freire de (2021)
This cross-sectional study aimed to evaluate the diagnostic accuracy of severe periodontitis by three different case definitions. Patients over 35 years (n = 243, mean age= 47.8±9.4 years) were evaluated by periodontal examinations and classified in severe periodontitis patients according to the CDC/AAP case definitions, the new periodontal disease classification (EFP/AAP), and the CPI. The primary outcome was to compare the diagnostic accuracy of severe periodontitis between the three case definitions. Sensitivity (SS), specificity (SP), and ROC curves were used to analyze the accuracy. The proportion of subjects presenting the most severe definitions of each classification was: severe periodontitis (CDC/AAP) = 47.3%, type III and IV periodontitis (EFP/AAP) = 43.2% and CPI code 4 = 44.4%. When comparing the CDC/AAP case definitions with the EFP/AAP classification, it was obtained SS, SP, and ROC of 81.7%, 91.4%, and 0.866 (CI 95%: 0.816-0.916), respectively. Similarly, when comparing CDC/AAP to CPI code 4, SS, SP, and ROC of 81.7%, 89.1%, and 0.854 (CI 95%: 0.802-0.906), respectively, were obtained. When type III and IV periodontitis (EFP/AAP) was compared to CPI code 4, the values were 92.4%, 92%, and 0.922 (CI 95%: 0.883-0.961), respectively. Both the new classification of periodontal diseases (EFP/AAP) and the CPI demonstrated high diagnostic accuracy with the CDC/AAP case definition to diagnose severe periodontitis. However, better accuracy and better ability to classify those patients with and without severe periodontitis were obtained between the EFP/AAP classification and the CPI.